PERKEMBANGAN ANAK USIA SEKOLAH DASAR: ASPEK KOGNITIF, SOSIAL, DAN EMOSIONAL - Aliyyah, Hanifah; Latifa, Lulu; Fadillah Rahmadianita, Nindy; Sukma, Elfia; Kharisma, Inggria (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Child development during elementary school is a crucial phase in the development of cognitive, social, and emotional abilities, which serve as the foundation for subsequent growth. Cognitive-wise, children experience improvements in logical thinking, understanding concrete concepts, and solving simple problems in an organized manner. Socially, children begin to learn to interact more broadly with peers, understand norms, and develop cooperation and empathy. Emotionally, children begin to recognize, regulate, and express feelings more appropriately, although they still require guidance from their surroundings. This study aims to examine in depth the development of elementary school-aged children in these three aspects and their relationship to the learning process. The method used is a literature review by analyzing various relevant sources using a qualitative approach. The findings of this study indicate that cognitive, social, and emotional development are interrelated and influence children's learning success. Therefore, an active role is needed from teachers and parents in creating an environment that can support children's optimal development.